A clinical study on the influence of suturing material on oral wound healing - Gazivoda, Dragan; Pelemiš, Dejan; Vujašković, Goran (Vojnosanitetski pregled, 2015)
Background/Aim. Suture materials play an important role in healing, enabling reconstruction and reassembly of tissue separated by the surgical procedure or trauma, and at the same time facilitating and promoting healing and hemostasis. Suture materials are used daily in oral surgery, and are considered to be substances most commonly implanted in human body. The aim of this clinical study was to examine the speed of wound healing and complications incidence, after the use of three different absorbable synthetic suture materials in oral surgery (catgut, Dexon and Vicryl rapide), and to ascertain which one is the most suitable for oral surgery. Methods. The study was conducted on 96 patients undergoing root resection or surgical extraction of third molars. Each of the suture materials (catgut, Dexon and Vicryl rapide) was used for 8 root resections and 8 surgical third molar extractions in the maxilla, as well as in the mandible (a total of 32 surgical interventions for each suture material). Results. The faster wound healing was obtained with Vicryl rapide compared to other two suturing material tested. There was no significant difference regarding the presence of local reaction in all the three groups of patients on the 21st postoperative day. Conclusion. The results of our clinical study point out that Vycril-rapid contributes more than catgut or Dexon to faster healing of human wounds, with fewer incidences of wound dehiscence and milder local reactions